SiPM-based optical sensing system for GIS partial discharge detection - Shiman Lin; Yusheng Chen; Deyu Qu; Yijia Ren; Xin Li; Jiangnan Liu (PLoS ONE, 2026)
The silicon photomultiplier (SiPM)-based optical detection method, which provides strong resistance to electromagnetic interference and high sensitivity, is attracting increasing attention. However, most studies have been conducted on laboratory simulation platforms, and few studies have systematically investigated SiPM-based partial discharge (PD) detection in actual gas insulated switchgear (GIS) equipment. In addition, the photon detection efficiency (PDE) of SiPMs varies with photon wavelength, and current studies lack a theoretical basis for the selection of SiPMs. To address this issue, an experimental platform for GIS gas discharge analysis was established in this study to systematically investigate the emission spectral characteristics of SF 6 gas discharge at different discharge intensities, pressures, and temperatures. On this basis, a SiPM-based optical sensing system adapted for GIS applications was developed. Ultimately, a PD detection experiment was conducted on an actual 110 kV GIS platform. The experimental results indicate that the detection signal-to-noise ratio of the developed SiPM-based optical detection system is approximately 5.8 dB higher than that of the high-frequency current transformer and that the minimum detectable discharge quantity is below 18 pC. These results highlight the potential of SiPM-based optical detection technology for GIS PD detection.